PRACTICE OF RACISM IN SOUTH AFRICA POST-APARTHEID - Suhanto, Suhanto; Zhouneil, Riesa (Universitas Nasional, 2021)
This paper aims to describe: First, the background of the rise of apartheid politics in South Africa. Second, the implementation of apartheid politics in South Africa in 2016-2019. Third, the reaction to the implementation of apartheid politics in South Africa in 2016-2019 and fourth, South Africa after the apartheid period. These four descriptions are to answer the main problem of the occurrence of racist practices in post-apartheid South Africa. The research method uses qualitative with international relations science approach. This research is a descriptive-analytic study, a research that uses a pattern of describing the state of empirical facts with descriptive arguments that are relevant. Then, the results of the description are followed by analysis to draw analytic conclusions. To identify and discuss this problem, the author uses the concept of national identity and racist theory and ethnicity theory. The results of this study indicate that: First, the emergence of apartheid politics in South Africa, was motivated by three things namely historical background, racial background of white supremacy and economic background. Second, the implementation of apartheid politics in South Africa in 2016-2019 was systematically institutionalized and contained in discriminatory laws and applied in various aspects of life, especially in the social, political and economic fields. Third, the reaction to the implementation of apartheid politics in South Africa in 2016-2019 came from within the country and abroad. Fourth, the situation in South Africa after apartheid is the emergence of Xenophobia and its impact on the economic, social and political fields. The practice of racism in South Africa still exists where they still consider racial and skin differences to be very strong and whites still feel they are superior to blacks. This has caused South Africa to be underdeveloped in the economic, political and social fields.